The incidence of lung cancer by histological type: A population‐based study in Tianjin, China during 1981–2005. Issue 8 (28th August 2014) - Kong, Jinyu; Xu, Fangxiu; He, Min; Chen, Kexin; Qian, Biyun
Abstract Background and objective Lung cancer remains the leading cause of cancer deaths worldwide. The aim of this study was to examine the trend in the incidence of lung cancer, validated by histology in Tianjin, the third largest municipal city in China, during the period from 1981 to 2005. Methods New lung cancer cases, crude incidence rates and age‐adjusted rates by histological type were analysed using the data from the Tianjin Cancer Registry, which covers a population of 4 million urban residents. Results The most common histological types of lung cancer were squamous cell carcinoma (SQCC) in men and adenocarcinoma (ADC) in women. During the 25‐year period, the constitutive pattern of the histological types changed gradually, ADC increased by 31.4%, but SQCC decreased by 25.6% among women. For SQCC, ADC or small cell carcinoma (SMCC), both the new cases and crude incidences per year increased among men and women. However, the age‐adjusted incidences of all types of lung cancer showed an initial increase, which then levelled off or declined in recent years. The birth‐cohort incidence analyses revealed that SQCC declined sharply, while ADC still increased among the younger age groups. Conclusion The incidences of lung cancer by histological type changed during the 25‐year period in Tianjin. Tailored strategies on prevention and control should be developed to meet the needs for various populations.